BS EN 61951-1 AMD1. Secondary cells and batteries containing alkaline or other non-acid electrolytes. Secondary sealed cells and batteries for portable applications. Part 1. Nickel-Cadmium (18th June 2021) - British Standards Institution,
No abstract available